Florida's Introduced Birds: European Starling (Sturnus vulgaris) - Steve A. Johnson; Walter Givens (EDIS)
WEC-255, a 6-page illustrated fact sheet by Steve A. Johnson and Walter Givens, introduces the European Starling — species description, similar species, native range and habitats, mode of introduction, introduced range and habitats, ecological impacts, impacts to people and pets, and solutions. Includes additional resources. Published by the UF Department of Wildlife Ecology and Conservation, April 2009.